The effect of couple-centered counseling based on EX-PLISSIT model on the sexual function of couples during pregnancy: a randomized controlled trial - Mahsa Fattahi; Seyedeh Zahra Masoumi; Farideh Kazemi; Mohammad Ahmadpanah (Kashan University of Medical Sciences, 2023)
Background: Sexual problems in couples during pregnancy can be attributed to changes in their sexual performance caused by physical and mental changes experienced during this period.Objectives: This study aimed to evaluate the impact of couple-centered counseling, using the EX-PLISSIT model, on the sexual function of couples throughout pregnancy.Methods: In 2022, a randomized clinical trial was conducted in Hamadan, Iran. The study included 60 couples, with an equal distribution of 30 couples in each group. The Female Sexual Function Index (FSFI) was completed by the women before and four weeks after the intervention, while the men filled out the International Index of Erectile Function (IIEF) during the same time frame. Couple-centered counseling sessions were conducted using the principles of EX-PLISSIT, with four sessions. The data was analyzed using t-test, paired t-test, and Wilcoxon test.Results: The mean FSFI and IIEF scores did not differ significantly between the two groups at baseline (P=0.16). After the intervention, the mean FSFI increased slightly in both groups, and this increase was statistically significant in both the intervention group (P<0.001) and the control group (P=0.01). Furthermore, after the intervention, the mean IIEF increased slightly in both groups, but the increase was statistically significant only in the intervention group (P<0.001).Conclusion: Counseling based on the EX-PLISSIT model can relatively improve the sexual performance of couples during pregnancy.